Humor and cultural values in print advertising: a cross-cultural study - Zotos, Yorgos; Hatzithomas, Leonidas; Boutsouki, Christina (My University, 2011)
Purpose – The present study aims to discuss the role of Hofstede’s cultural dimensions, uncertainty avoidance and individualism/collectivism, on the use of various humor types in print advertising, across culturally diverse countries. Design/methodology/approach – A sample of 12,351 ads (3,828 humorous) from the largest circulated UK and Greek magazines was content-analyzed in light of Speck’s humorous message taxonomy, emphasizing humor types and intentional relatedness. Findings – The results indicate that cultural diversity is reflected in the types of humorous devices that tend to be used in the UK and Greece. British advertisements incorporate not only sentimental but also disparaging humor types such as sentimental humor and full comedy, providing a great deal of pure entertainment. On the contrary, Greek print ads emphasize cognitive humorous appeals, in an attempt to provide credible information to the uncertainty-avoiding Greek audience. Practical implications – The findings of this study highlight some key aspects of UK and Greek print advertising that can be extended in other homogeneous cultures. In individualistic countries with low uncertainty avoidance, it seems that consumers prefer humor-dominant messages. On the contrary, in collectivistic countries with high uncertainty-aversion attitudes, humor can be used as a Trojan horse to convey the required information to the target group. Originality/value – The present study points out how advertisers’ intentions to entertain or to inform the target audience are expressed in the use of various humor types in advertising, underlining, also, the effect of cultural values on these communication decisions.
Keywords: Humour; National cultures; Advertising; United Kingdom; Greece